Questions About Angels - Collins, Billy (Book collections on Project MUSE., 1999)
Billy Collins -- winner of a Guggenheim Fellowship, veteran of a one-hour Fresh Air interview with Terry Gross, and a guest on Garrison Keillor's Prairie Home Companion -- arrives at Random House with the poetic equivalent of a Greatest Hits album, seasoned with some wonderful new numbers. Ranging from a lament over "Forgetfulness"--"Whatever it is you are struggling to remember/it is not poised on the tip of your tongue, /not even lurking in some obscure corner of your spleen"--to a love poem that starts with weighing a dog, to a definitive "Life of Riley" ("He never had a job, a family or a sore throat"), Billy Collins' poems often seem modest and homespun, until the reader finds himself suddenly dissolving into laughter or tears. As for his popularity, a recent piece in Publishers Weekly, which ran before his three-book deal with Random House was made public, will perhaps be more convincing than any editor trying to flog a book in a fact sheet could be: "In February alone, three of Collins' collections sold nearly 8000 copies ... Fresh Air/Terry Gross recently rebroadcast an hour-long interview with Collins; the following day Picnic, Lightning briefly hit #59 in Amazon.com's bestseller rankings." Billy Collins is a dynamic and popular reader. He makes between thirty and forty appearances a year. His arrival at a prominent trade publishing house will ensure an even wider audience for his poetry and will capitalize on his increasing popularity. Household name may not be too much to ask for